Respuesta :
Answer:
Option (b) is correct.
The expression is equivalent, but the [tex]a^2-4[/tex] term is not completely factored.
Step-by-step explanation:
Given : a student factors [tex]a^6-64[/tex] to [tex](a^2-4)(a^4+4a^2+16).[/tex]
We have to choose the correct statement about [tex](a^2-4)(a^4+4a^2+16).[/tex] from the given options.
Given [tex]a^6-64[/tex] is factored to [tex](a^2-4)(a^4+4a^2+16).[/tex]
Consider [tex]a^6-64[/tex]
Using algebraic identity, [tex]a^3-b^3=(a-b)(a^2+ab+b^2)[/tex]
comparing [tex]a=a^2[/tex] and b = 4, we have,
[tex](a^2)^3-4^3=(a^2-4)(a^4+4a^2+16)[/tex]
Thus, the factorization is equivalent but we can simplify it further also, as
Using algebraic identity, [tex]a^2-b^2=(a+b)(a-b)[/tex]
Thus, [tex]a^2-4=a^2-2^2[/tex]
Can be written as [tex]a^2-4=(a+2)(a-2)[/tex]
Thus, the expression is equivalent, but the [tex]a^2-4[/tex] term is not completely factored.
Option (b) is correct.